The Factors That Influence Customer Satisfaction to Use Malaysia Airlines in Malaysia - Liem Gai Sin; Lok Yee Huei; Livia Loh Xin Yuu; Looi Kai Yi; Liu Qifeng; Liu Fanxi; Liu Xinyu; Manogna C V L; A. J. Ali; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
Improving customer satisfaction is key to being competitive in the Airline industry. This research aimed to study the factors that influence customer satisfaction to use Malaysia Airlines in Malaysia. Malaysia Airways Limited began its first commercial flight in year 1947 and was renamed become Malaysian Airline System in year 1972. Malaysia Airlines operates scheduled domestic and international flights to more than 1000 destinations across 150 plus countries. A quantitative approach with a survey questionnaire was used for data collection. A total of 100 Malaysia Airlines customers participated in this survey. In this survey, five influencing factors are assessed which is airline tangibles, personnel quality, empathy, and airline image. Through a comprehensive analysis of customer feedback, personnel quality, and empathy are the most important factors in improving customer satisfaction to use Malaysia Airlines in Malaysia. This survey provides Malaysia Airlines with useful insights into customer perception and guides Malaysia Airlines in improving customer satisfaction